Correlation Between History of ISTC Training on Independent Practicing Doctor With Discovery of TB Suspected Children in Surabaya City - Madu Puspita Nuansa Jatu; Fariani Syahrul (Health Notions, 2018)
The burden of Tuberculosis in children cases in the world is unknown due to the lack of diagnostic tools that are "child friendly" and the inadequacy of recording and reporting systems. TB findings in East Java province is second only to west java and the highest number of cases is in Surabaya. The purpose of this study was to analyse the relationship between history of ISTC training with the discovery of TB suspected Children. This research was done with case control design. The case samples were 14 doctors who found suspected TB in children and control sample that was 56 doctors which did not find suspected TB in children. Sampling technique was simple random sampling. Data analysis using Odds Ratio (OR) and 95% CI. The results of the analysis showed that OR value = 5.222 (95% CI 1.470